The influences of socio-cultural characteristics on public low-cost residents’ satisfaction: a case study on PPR Seri Aman Kuala Lumpur, Malaysia - Mahdzir, Mazura (Enviro Research Publishers, 2022)
The development of housing often needed to be considered both economic and socio- cultural elements. Certain variables, such as residents' experience and socio-cultural backgrounds, have influenced how people perceive their living environment. Past researchers have highlighted several issues associated with low-cost housing and showed that Malaysia's housing policies still failed to provide a comfortable living area for the low- cost income group. Moreover, previous studies mainly focused on the residents' demographic characteristics as the influential factors. Therefore, this paper tries to fill this gap by (i) identify the socio-cultural characteristics of residents (ii) analyse the relationship between residents’ satisfaction and their socio-cultural characteristics. This is important since the study related to this aspect remains insufficient and their characteristics might affect the level of satisfaction of residents in terms of housing necessity. Based on the purposive sampling, the low-cost housing residents were selected. A questionnaire survey has been conducted on 93 residents of PPR Seri Aman in Kuala Lumpur and the data was analyzed using factor analysis and Pearson's correlation analysis. Findings from the study revealed that the residents were fairly satisfied with the dwelling unit features and neighborhood facilities. The low level of satisfaction among residents was heavily influenced by the yard, kitchen, dining space, parking available, sidewalks and connectivity of paths, traffic nearby, and the distance to take public transport. Further suggestions or recommendations are proposed to improve these situations or to help for future development planning.